Manajemen Kurikulum dalam Pembelajaran Jarak Jauh di Masa Pandemi COVID-19 - Adi Syaputra; Enung Hasanah (Kelola: Jurnal Manajemen Pendidikan, 2021)
During the COVID-19 pandemic, there has been a change in learning patterns from face-to-face systems to distance learning systems. This requires innovation and creativity from school principals in order to build an effective curriculum for distance learning. This study aims to examine school curriculum management in distance learning during the COVID-19 Pandemic. The method used in this research is a qualitative research method by using literature that are in accordance with the theory discussed in the scope of curriculum management in distance learning and also analyzes cited scientific articles using google scholar with keywords Curriculum; Strategy; SMK; Online Learning; Emergency Curriculum, Learning Management, Learning Effectiveness. The results show that in implementing curriculum management in distance learning during the COVID-19 pandemic, one must pay attention to the conditions of each region and different schools so that the predetermined goals can be achieved. Curriculum management in distance learning during the COVID-19 pandemic that was implemented by schools had 4 scopes, namely: 1) planning; 2) organizing; 3) implementation; 4) evaluation. Planning that is carried out must be in accordance with the distance learning model and use essential basic competencies, in organizing must design learning activities in accordance with the conditions and time allocation and those related to increase the effectiveness of the teaching and learning process, while in implementation it requires teachers and students to be adaptive and innovative in using technology. So that learning is effective, as well as the evaluation is carried out applied with aspects of attitude, aspects of knowledge, aspects of skills to determine the extent to which school programs have been implemented.